The Violation of Bureaucracy at Local Election in Gowa South Sulawesi: Based on Weberian and Marxism Concept - Wiwid Ambarwati; Gustiana Anwar Kambo; Muhammad Muhammad (ARISTO, 2020)
State civil apparatus has mobilized by a pair of the candidate, Ichsan Yasin Limpo and Andi Mudzakkar (IYL-Cakka) on the 2018 South Sulawesi Local Election in Gowa was very structured and massive. That case is proved by the victory of Them in Gowa around 68.38 percent. The support from Gowa's society for the nominating process is 260 650 IYL-Cakka identity. Based on the result of administrative verification showed that 0.5 percent are civil state apparatus's identity and the result of factual verification is 1.53 percent. Meanwhile, the state civil Also apparatus supported them with symbols of the candidate. It’s proved by a report of 37 cases of neutrality violation to the South Sulawesi Provincial of the General Election Supervisory. This research method used a descriptive case study approach. The Data on this research used primary and secondary data. The data were collected from several methods: observation, interviews, and documentary. The result of this study indicated resources that supported instruction to them have consisted of two categories: 1) the instruction to the collected identity cards and 2) the instruction to used symbols. The identity cards were collected by three elements: the winning team for IYL-Cakka, the Headman and their staffs, and the other elements (agricultural extension workers and educators). The instruction to used symbols created has been done with the group in social media for all of the government head offices and created the formal regular meetings outside the Gowa (like as benchmarking).